Mechanically Guided Post‐Assembly of 3D Electronic Systems. (25th September 2018) - Kim, Bong Hoon; Liu, Fei; Yu, Yongjoon; Jang, Hokyung; Xie, Zhaoqian; Li, Kan; Lee, Jungyup; Jeong, Ji Yoon; Ryu, Arin; Lee, Yechan; Kim, Do Hoon; Wang, Xueju; et al.
Abstract: This paper describes deterministic assembly processes for transforming conventional, planar devices based on flexible printed circuit board (FPCB) platforms into those with 3D architectures in a manner that is fully compatible with off‐the‐shelf packaged or unpackaged component parts. The strategy involves mechanically guided geometry transformation by out‐of‐plane buckling motions that follow from controlled forces imposed at precise locations across the FPCB substrate by a prestretched elastomer platform. The geometries and positions of cuts, slits, and openings defined into the FPCB provide additional design parameters to control the final 3D layouts. The mechanical tunability of the resulting 3D FPCB platforms, afforded by elastic deformations of the substrate, allows these electronic systems to operate in an adaptable manner, as demonstrated in simple examples of an optoelectronic sensor that offers adjustable detecting angle/area and a near‐field communication antenna that can be tuned to accommodate changes in the electromagnetic properties of its surroundings. These approaches to 3D FPCB technologies create immediate opportunities for designs in multifunctional systems that leverage state‐of‐the‐art components. Abstract : Buckling‐induced processes for geometry transformation provide routes to 3D flexible printed circuit board (FPCB) technologies as device platforms with electrically and mechanically adaptable properties. These schemes, taken together with accurate simulation tools, provide simple and versatile means to access 3D designs in FPCB platforms, in ways that are fully compatible with off‐the‐shelf device components.